The inefficiency of price taking behavior in multiperiod production economies with incomplete markets - Egbert Dierker (Institute for Advanced Studies (IHS), 2012)
The purpose of this paper is to explore how the concept of a Drèze equilibrium can be extended to multiperiod production economies with incomplete markets. Constrained efficiency cannot serve as a basis for such an extension because multiperiod models tend to violate even weak constrained efficiency requirements. We show by means of examples how the difficulties that arise in the case of sequential trade can be taken into account. Finally, we employ the concept of minimal efficiency, which has been introduced by Dierker et al. (2005) in a two-period model, to derive a natural extension of the Drèze rule. This is possible because minimal efficiency relies on a planner who can choose the production plan but who cannot interfere with future consumption otherwise.
Keywords: D21; D52; D61; 330; incomplete markets with production; the objective of a firm; Drèze equilibria with sequential trade; efficiency and social welfare